PENGARUH SERBUK CANGKANG TELUR TERHADAP SIFAT MEKANIS BETON DAUR ULANG - Kharismalsyah Maulana Akbar; Resti Nur Arini (Politeknik Negeri Jakarta, 2023)
In Indonesia, normal concrete construction is commonly used in the construction process. Excessive concrete waste is usually uncontrolled. Laboratory concrete testing waste can also accumulate and disturb the ecosystem and reduce the aesthetic value of a place. There have been many studies using recycled aggregate from concrete waste. Meanwhile, eggs are one of the foods frequently consumed by Indonesian. Eggshells are certainly becoming waste. According to data from the Indonesia Statistics (2019), chicken egg production in Indonesia reached 4,688,120 tons. Eggshell contains about 94% calcium carbonate with a weight of 5.5 grams. Meanwhile, calcium carbonate is the main constituent of Portland cement, accounting for 70% of other constituents. Based on the reasons above, this study was conducted to determine the effect of chicken eggshell powder as a partial replacement for cement on the mechanical properties of concrete with recycled coarse aggregate. The variations in the use of chicken eggshells in the concrete samples were 0%, 2.5%, 5%, 7.5%, and 10% of the weight of cement. To determine the mechanical properties of the concrete, compressive and splitting tensile tests were conducted using a cylindrical test specimen with a size of 10 x 20 cm. It is expected that the use of chicken eggshell powder can increase the compressive strength of recycled concrete. Based on the test results, the compressive strength of the concrete composition with 2.5% eggshell powder showed the greatest increase compared to the other compositions. This is supported by the UPV test, which showed the same result. The largest increase in splitting tensile strength was also found in the 2.5% composition. Meanwhile, good homogeneity levels were obtained in the concrete, based on the UPV test results on the test specimens at the age of 28 days.